The attitude of Teachers Towards Delayed Students in Mainstream Classrooms at Elementary Level in Pakistan - Dr. Wajiha Kanwal; Dr. Cedric Aimal Edwin; Dr. Sana Aroos Khattak; Nadia Mahrukh (Journal of Management Practices, Humanities and Social Sciences, 2021)
After becoming a signatory of UNCRPD, inclusive education is a reality for approaching days; however, due to our already weak and socio-religiously confused educational system, teachers and parents of delayed students, are not ready to accept them in mainstream classrooms. The basic reason for such reluctance is lack of awareness and fears of added responsibilities, which may be associated with this major shift in educational methodology. The aim of the research is to understand the attitude and perception of teachers about the inclusive education concept. In this study, mixed-method research (both qualitative and quantitative) was used. The research instrument was developed according to the directions and guidance provided by experts with fourteen items, which were then shared with 100 elementary school teachers belonging from different Federally administered educational institutions in District Okara, and their responses were quantified for analysis. Moreover, interviews of senior teachers from the same educational institutions were also conducted to obtain a clear perspective of the issue. Convenience sampling techniques were used, and descriptive analysis was used to assess responses. Based on acquired data, results were finalized, which showed reluctance by teachers due to lack of awareness as well as fear of additional responsibilities and expectations without any visible incentive. Moreover, neither required human resources nor infrastructures allow an inclusive schooling system to be adopted. Thus, a gradual approach towards implementation of a new concept along with concrete steps by the government is found to be the most viable option for approaching the issue.